Twisted Tensor Products of Kn with Km - Arce, Jack (2018)
We find three families of twisting maps of Km with Kn, where K is a field, and we make a detailed study of its properties. One of them is related to truncated quiver algebras, the second one consists of deformations of the first and the third one requires m = n and yields algebras isomorphic to Mn(K).